A New Hole Transport Material for Efficient Perovskite Solar Cells With Reduced Device Cost. Issue 1 (22nd December 2017) - Sun, Yuhao; Wang, Changlei; Zhao, Dewei; Yu, Jiangsheng; Yin, Xinxing; Grice, Corey R.; Awni, Rasha A.; Shrestha, Niraj; Yu, Yue; Guan, Lei; Ellingson, Randy J.; Tang, Weihua; et al.
Abstract : To realize commercialization of perovskie solar cell (PVSC) technology, it is essential to reduce the device costs while maintaining high power conversion efficiencies (PCEs). So far, the high cost of the most commonly used hole selective material, 2, 2′, 7, 7′‐Tetrakis (N, N‐di‐p‐methoxyphenylamino)‐9, 9′‐spirobifluorene (spiro‐OMeTAD), for high‐PCE PVSCs presents a significant obstacle for device cost reduction. In this work, the synthesis and characterization of a new spiro‐OMeTAD derivative hole selective material, 2, 6, 14‐tris(5′‐(N, N‐bis(4‐methoxyphenyl)aminophenol‐4‐yl)‐3, 4‐ethylenedioxythiophen‐2‐yl)‐triptycene (TET) is reported. TET features a three‐dimensional structure consisting of a triptycene core and triarylamine arms linked by 3, 4‐ethylenedioxythiophene, facilitating efficient hole transport. Planar PVSCs using TET hole selective layers (HSLs) achieved high fill factors of over 81% and steady‐state efficiencies of up to 18.6%, comparable with that (19.0%) of PVSC using spiro‐OMeTAD HSL. Importantly, the hereby reported efficient PVSCs can be produced with very thin TET HSLs (about 30 nm). Considering the lower laboratory synthesis and purification cost ($123 vs. $500 g −1 ) and thinner HSL (30 vs. 200 nm), the cost for TET on a unit area of one device is 25 times lower than that for high‐purity spiro‐OMeTAD. The device with TET HSL shows good stability under continuous illumination. Therefore, this work makes a significant step forward toward the commercialization of the emerging PVSC technology. Abstract : New triptycene‐derived hole transport material (HTM) TET is developed for efficient perovskite solar cells (PVSCs). Planar PVSCs with ≈30 nm TET achieve a maximum power conversion efficiency of 19.1% and a steady‐state efficiency of 18.6%, comparable with those using 200 nm spiro‐OMeTAD. The use of thinner TET HTM cuts the device cost by 25 times, compared with that using spiro‐OMeTAD.